Membrane trafficking alterations in breast cancer progression - Ferreira, Andreia; Castanheira, Pedro; Escrevente, Cristina; Barral, Duarte C.; Barona, Teresa (Frontiers in Cell and Developmental Biology, 2024)
Breast cancer (BC) is the most common type of cancer in women, and remains one of the major causes of death in women worldwide. It is now well established that alterations in membrane trafficking are implicated in BC progression. Indeed, membrane trafficking pathways regulate BC cell proliferation, migration, invasion, and metastasis. The 22 members of the ADP-ribosylation factor (ARF) and the >60 members of the rat sarcoma (RAS)-related in brain (RAB) families of small GTP-binding proteins (GTPases), which belong to the RAS superfamily, are master regulators of membrane trafficking pathways. ARF-like (ARL) subfamily members are involved in various processes, including vesicle budding and cargo selection. Moreover, ARFs regulate cytoskeleton organization and signal transduction. RABs are key regulators of all steps of membrane trafficking. Interestingly, the activity and/or expression of some of these proteins is found dysregulated in BC. Here, we review how the processes regulated by ARFs and RABs are subverted in BC, including secretion/exocytosis, endocytosis/recycling, autophagy/lysosome trafficking, cytoskeleton dynamics, integrin-mediated signaling, among others. Thus, we provide a comprehensive overview of the roles played by ARF and RAB family members, as well as their regulators in BC progression, aiming to lay the foundation for future research in this field. This research should focus on further dissecting the molecular mechanisms regulated by ARFs and RABs that are subverted in BC, and exploring their use as therapeutic targets or prognostic markers.